Descendable maps of schemes and generators of derived categories - Zhao, Jiayu (My University, 2025)
This work establishes the theory of descendable morphisms of schemes which were previously introduced by Akhil Mathew for stable [infinity]-categories. We prove properties they have, provide examples, and discuss applications to dimension theory. We explore the connection between descendable maps and generators of derived categories of quasi-coherent sheaves.
Keywords: Descendable maps; Triangulated categories; Rouquier dimension